2015
DOI: 10.1080/23743670.2015.1119487
|View full text |Cite
|
Sign up to set email alerts
|

Africa in the click stream: audience metrics and foreign correspondents in Africa

Abstract: Citation: Bunce, M. (2015). Africa in the click stream: audience metrics and foreign correspondents in africa. African Journalism Studies, 36(4), pp. 12-29. doi: 10.1080/23743670.2015.1119487 This is the accepted version of the paper.This version of the publication may differ from the final published version. selection and development of news stories. Drawing on 67 interviews with foreign correspondents in East and West Africa, the article identifies three different approaches to audience metrics: correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…This article draws on data from a 2-month observation period in the Reuters Nairobi bureau in 2009, and semi-structured interviews with the 10 text journalists routinely working in the newsroom. This research was conducted as part of a larger project looking at international news production in sub-Saharan Africa, completed between 2008 and 2014 (Bunce 2013, 2015). The Reuters East Africa bureau is a modern office on the 12th storey of Finance House in downtown Nairobi.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This article draws on data from a 2-month observation period in the Reuters Nairobi bureau in 2009, and semi-structured interviews with the 10 text journalists routinely working in the newsroom. This research was conducted as part of a larger project looking at international news production in sub-Saharan Africa, completed between 2008 and 2014 (Bunce 2013, 2015). The Reuters East Africa bureau is a modern office on the 12th storey of Finance House in downtown Nairobi.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, increasingly fragmented or hybrid professionalisms raise questions about the ongoing influence of industry norms more generally (Ornebring et al, 2014). Partial professionalism is particularly common in the international news system, which relies heavily on local stringers and fixers who are not generally trained as journalists, and who may primarily seek financial rewards for their work, rather than professional accolades (Bunce, 2013; Murrell, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Already present and salient frames and narrative genres that highlight good and bad guys or the audiences’ moral obligation to do something or to care are often relied upon to make this connection (Entman, 2004; Moeller, 1999). In the age of online readership, this connection is created through the use (and insertion by some editors) of words and phrases readers are already searching for on Google or likely to do so (see Bunce, 2015: 19). In the effort to domesticate foreign news on atrocity, coverage may misrepresent, and misunderstand, the nature of an unfolding atrocity (Atkinson, 1999; Chin-Chuan et al, 2002; Moeller, 1999).…”
Section: Domesticating Foreign Realities For a Local Audiencementioning
confidence: 99%
“…For instance, in one of the first studies of this kind, Usher (2013) found that at Al-Jazeera English, a lack of organizational norms and policy led journalists not to equate more hits with journalistic success or status. Bunce (2015; 2017) found that, based on readership, Reuters’ managers praised or censured their journalists (cf. Tandoc, 2015).…”
mentioning
confidence: 99%